2017
DOI: 10.1155/2017/4807163
|View full text |Cite
|
Sign up to set email alerts
|

Central Precocious Puberty and Response to GnRHa Therapy in Children with Cerebral Palsy and Moderate to Severe Motor Impairment: Data from a Longitudinal, Case-Control, Multicentre, Italian Study

Abstract: Background Children affected by neurodevelopmental disability could experience early pubertal changes at least 20 times more than the general population. Limited data about central precocious puberty (CPP) among children affected by cerebral palsy (CP) are available. Methods This is a longitudinal, observational, retrospective, case-control study involving 22 children affected by CPP and CP (group A), 22 paired with CP but without CPP (group B), and 22 children with CPP without CP. Auxological, biochemical, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…The prevalence of CPP in children with cerebral palsy and moderate or severe motor impairment is unknown, as the available data are limited (15,33,34). A higher prevalence of variable degrees of early sexual maturation was reported in 161 girls with neonatal encephalopathy As expected, our patients also frequently displayed other types of alteration to brain structure (data not shown).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The prevalence of CPP in children with cerebral palsy and moderate or severe motor impairment is unknown, as the available data are limited (15,33,34). A higher prevalence of variable degrees of early sexual maturation was reported in 161 girls with neonatal encephalopathy As expected, our patients also frequently displayed other types of alteration to brain structure (data not shown).…”
Section: Discussionsupporting
confidence: 49%
“…It has been suggested that severe brain damage and antiepileptic drugs probably affect neurotransmitter pathways involved in gonadotropin control and that the normal hypothalamic inhibition of gonadotropins may be lost (34). Limited data have also been reported for patients with RASopathies and CPP, such as our patients with cardio facio cutaneous syndrome (BRAF mutation) (19, 36) or epidermal nevus syndrome with HRAS gene mutation (37,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…NI children could experience disorders of puberty in term of precocious or delayed puberty. Pediatric patients affected by neurodevelopmental disabilities are 20 times more at risk of premature pubertal changes compared to the general population (4). Many insults to the central nervous system including birth asphyxia, congenital malformation and infections can cause PP (4).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients affected by neurodevelopmental disabilities are 20 times more at risk of premature pubertal changes compared to the general population (4). Many insults to the central nervous system including birth asphyxia, congenital malformation and infections can cause PP (4). Severe brain damage and use of antiepileptic medication may affect a number of neurotransmitter pathways involved in gonadotropin control, inducing an activation of the hypothalamic-pituitary-gonadal axis (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation